2005
DOI: 10.1007/s10499-005-9020-3
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory and hematological response of tench, Tinca tinca (L.) to a short-term cadmium exposure

Abstract: The effects of 3 h exposure to 96hLC50 of cadmium (4.5 mg dm )3 ) on oxygen consumption rate, and hematological parameters (RBC, WBC, erythrocyte and leukocyte pattern) of juvenile tench were evaluated. Oxygen consumption significantly decreased beginning from 24 h postexposure, and remained reduced until the end of the experiment (96 h postexposure). RBC gradually increased, together with the percentage of juvenile cells in circulation. On the other hand, cadmium induced damage to the red cells -the share of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Alwan [24] reported that the stimulation of erythropoiesis or the disturbances that occurred in both metabolic and hemopoietic activities of fish exposed to sub lethal concentrations of aluminium are defense reaction against toxicity of aluminium. Presence of cadmium in water and its significant levels in fish tissues (muscle & gills) from lake B may cause disturbances in respiration as was also observed in tuna exposed for a short term period to cadmium by Witeska et al [25]. This trace metal affects the physiology of fish due to its chronic exposure to waterborne sub-lethal levels cadmium as suggested by Ricard et al [26] in the rainbow trout and by Abedi et al [27] in common carp.…”
Section: Discussionmentioning
confidence: 84%
“…Alwan [24] reported that the stimulation of erythropoiesis or the disturbances that occurred in both metabolic and hemopoietic activities of fish exposed to sub lethal concentrations of aluminium are defense reaction against toxicity of aluminium. Presence of cadmium in water and its significant levels in fish tissues (muscle & gills) from lake B may cause disturbances in respiration as was also observed in tuna exposed for a short term period to cadmium by Witeska et al [25]. This trace metal affects the physiology of fish due to its chronic exposure to waterborne sub-lethal levels cadmium as suggested by Ricard et al [26] in the rainbow trout and by Abedi et al [27] in common carp.…”
Section: Discussionmentioning
confidence: 84%
“…Immunotoxicological effects of Cd have been reported in various aquatic animals. In fish, Cd reduced numbers of white blood cells and induced blood cell deformation (Witeska et al 2006) and lymphocyte mortality (Witeska & Wakulska 2007), leading to higher intensities of monogenean and protozoan parasites (Hoole 1997, Khan 2003, Sanchez-Ramirez et al 2007. Similarly, short-term exposure to high concentrations of Cd significantly increased the encystment of a trematode parasite Echinoparyphium recurvatum in its first intermediate host, the snail Lymnaea peregra (Morley et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The number of red blood cells constantly increased for 96 hours after exposure, when the experiment reached its end, whereas the white blood cell number progressively decreased without changes in the lymphocytes/neutrophiles ratio, both parameters being significantly modified in comparison to the control group. With regard to blood cells, the numbers of structural abnormalities significantly increased, for instance abnormally shaped cells, intracellular vacuolation, cell swelling and disintegration of nuclear chromatin (Witeska et al, 2006).…”
Section: Metabolic Bioproductive and Reproductive Effects Of Cadmiummentioning
confidence: 99%